APPLICATION ACCEPTANCE OF HOSPITAL PATIENTS PERTAMINA CENTRAL HOSPITAL USING VISUAL BASIC 6.0 - Mustain Mustain; Sutarno, SKom, MMSI Sutarno, SKom, MMSI (Jurnal Sistem Informasi, 2003)
In scientific research, this writer attempts to solve the problems that occurred inpatients receiving inpatient activity. The problem in question is not efficient whencarried out activities that inpatient admission at the time of receipt, the officer mustwrite the transaction into several books. Microsoft Visual Basic is very supportive ofmaking an application that can alter a patient receiving a manual system to acomputerized system.Hospital patients receiving application is expected to help improve services, in thiscase the patient does not need to worry when booking a room.